Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/117
|View full text |Cite
|
Sign up to set email alerts
|

When Image Denoising Meets High-Level Vision Tasks: A Deep Learning Approach

Abstract: Conventionally, image denoising and high-level vision tasks are handled separately in computer vision. In this paper, we cope with the two jointly and explore the mutual influence between them. First we propose a convolutional neural network for image denoising which achieves the state-of-theart performance. Second we propose a deep neural network solution that cascades two modules for image denoising and various high-level tasks, respectively, and use the joint loss for updating only the denoising network via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 22 publications
0
106
0
Order By: Relevance
“…Recently, the authors of [155] proposes to realize task-based quality metric by "hooking" a image reconstruction network from unrolling dynamics with a image analysis DNN, so that the reconstructed images by the first network will be implicitly evaluated by the second which effectively makes the quality metric task-based. Similar idea appeared in computer vision for image denoising [94,93]. On the other than, these work also suggested a new "raw-to-task" modeling philosophy with encouraging empirical results.…”
Section: Deep Models In Medical Image Reconstructionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recently, the authors of [155] proposes to realize task-based quality metric by "hooking" a image reconstruction network from unrolling dynamics with a image analysis DNN, so that the reconstructed images by the first network will be implicitly evaluated by the second which effectively makes the quality metric task-based. Similar idea appeared in computer vision for image denoising [94,93]. On the other than, these work also suggested a new "raw-to-task" modeling philosophy with encouraging empirical results.…”
Section: Deep Models In Medical Image Reconstructionmentioning
confidence: 54%
“…The most simple and natural way of joining image reconstruction and image analysis is to connect the two networks together and conduct end-to-end training (from scratch or by fine-tuning). Such idea was first introduced by [155] in medical imaging and by [94,93] in computer vision for image denoising. By doing so, the second network for image analysis can be regarded as a task-based image quality metric that is learned from the data.…”
Section: Raw-to-taskmentioning
confidence: 99%
“…In [40,142], the joint optimization pipeline for low-resolution recognition is examined. In [41,42], Liu et al discussed the impact of denoising for semantic segmentation and advocated their mutual optimization. Lately, in [143], the algorithmic impact of enhancement algorithms for both visual quality and automatic object recognition is thoroughly examined, on a real image set with highly compound degradations.…”
Section: Visual Recognition Under Adverse Conditionsmentioning
confidence: 99%
“…Yet it remains questionable whether restoration-based approaches would actually boost the visual understanding performance, as the restoration/enhancement step is not optimized towards the target task and may bring in misleading information and artifacts too. For example, a recent line of researches [8,[39][40][41][42][43][44][45][46][47][48] discuss on the intrinsic interplay relationship of low-level vision and high-level recognition/detection tasks, showing that their goals are not always aligned.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has also been interest in designing image restoration and enhancement methods with the overall goal of improving high-level computer vision performance rather than perceptual image quality [10,11]. Earlier work showed how image degradations affect image recognition accuracy [12], how conventional low-level image restoration techniques do not necessarily improve the computer vision performance [10,13], and how jointly handling image restoration and recognition tasks can improve the results [10,11,14]. It has also been shown that imaging devices can save power when they are used for computer vision tasks by running in a lower resolution and precision mode and skipping processing steps that are traditionally used for enhancing image quality [13].…”
Section: Related Workmentioning
confidence: 99%